Revalidation of the milliped genus Amplaria Chamberlin 1941 (Diplopoda, Chordeumatida, Striariidae), and description of two new species from caves in Sequoia and Kings Canyon National Parks, California - Shear, William A.; Krejca, Jean K. (Zootaxa, 2007)
The milliped genus Amplaria Chamberlin 1941 was synonymized with Striaria Bollman 1888 by Hoffman (1980). Examination of a much wider range of materials of nominal Striaria species both from eastern North America and the Pacific coastal states shows that some species occurring from California to Washington (state) represent a distinct phyletic line, for which Amplaria Chamberlin 1941 is the oldest available generic name. Speostriaria Causey 1960 is a synonym of Amplaria. Amplaria muiri n. sp. and A. adamsi n. sp. are two new, recently discovered species from caves in Sequoia and Kings Canyon National Parks, California. Illustrations are provided of a specimen that may represent the type species, Amplaria eutypa (Chamberlin) 1953.